Edukasi Fikih Wanita Sejak Dini: Studi Implementasi Diklat Risalatul Mahid di SDN 02 Kemiri Ponorogo - Muhimmatul Mukaromah; Irin Putri Setiani; Syifa Nur ‘Afiah; Zulfa Fauziah (Muaddib: Jurnal Pendidikan Agama Islam, 2026)
Early female fiqh education is important for girls to understand the biological changes they experience when they reach puberty, particularly those related to menstruation. This study aims to describe the implementation of Risalatul Mahid Training as a form of female fiqh education at SDN 02 Kemiri Ponorogo. The method used was Participatory Action Research (PAR), involving teachers, students, and a team of Community Service Lecture (KPM) students in every stage of the activity, from planning to evaluation. The results showed that the training was able to improve female students' understanding of the basic concepts of menstruation, related fiqh laws, and attitudes towards maintaining cleanliness and worship during menstruation. This activity received a positive response because it was delivered using an interactive approach, was easy to understand, and suited to the developmental needs of children's ages. These findings indicate that early female fiqh education can be an important first step in equipping female students to face puberty with greater readiness and confidence.